(untitled) (Móin-Móin Magazine - Studies in the Art of Puppetry, 2026)
The interview with Anak Agung Gede Oka Dalem offers an in-depth overview of the formation and consolidation of the Peliatan style of legong, from its arrival from Sukawati to its international dissemination. The testimony highlights the fundamental roles of masters such as I Wayan Lotring, Gusti Biang Sengog, and Anak Agung Gde Mandera, emphasizing the technical and expressive elements that define the local identity. Oka underscores the continuity of the style and the responsibility of preserving the inherited lineage in the face of sociocultural and educational changes.